2013
DOI: 10.1016/j.cmet.2012.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Downregulation of Mitochondrial Function in Down Syndrome

Abstract: SUMMARY Mitochondrial dysfunction and oxidative stress are common features of Down syndrome (DS). However, the underlying mechanisms are not known. We investigated the relationship between abnormal energy metabolism and oxidative stress with transcriptional and functional changes in DS cells. Impaired mitochondrial activity correlated with altered mitochondrial morphology. Increasing fusion capacity prevented morphological but not functional alterations in DS mitochondria. Sustained stimulation restored mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
115
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 139 publications
(136 citation statements)
references
References 24 publications
15
115
0
1
Order By: Relevance
“…Previous work showed that multiple cellular functions are sensitive to mitochondrial failure in DS cells (Coskun et al, 2016; Helguera et al, 2013). To assess the potential functional recovery afforded by mCAT, we analyzed cellular proliferation and motility in a wound‐healing assay.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Previous work showed that multiple cellular functions are sensitive to mitochondrial failure in DS cells (Coskun et al, 2016; Helguera et al, 2013). To assess the potential functional recovery afforded by mCAT, we analyzed cellular proliferation and motility in a wound‐healing assay.…”
Section: Resultsmentioning
confidence: 97%
“…We recently reported chronic downregulation of mitochondrial activity in DS cells as an adaptive response to minimize oxidative damage and preserve basic cellular functions (Busciglio et al, 2002; Helguera et al, 2013). We further examined mitochondrial function and structure in DS HF and Dp16 MEF.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations